2021
DOI: 10.1111/sum.12736
|View full text |Cite
|
Sign up to set email alerts
|

Bio‐mediated soil improvement: An introspection into processes, materials, characterization and applications

Abstract: For a long time in the practice of geotechnical engineering, soil has been viewed as an inert material, comprising only inorganic phases. However, microorganisms including bacteria, archaea and eukaryotes are ubiquitous in soil and have the capacity and capability to alter bio‐geochemical processes in the local soil environment. The cumulative changes could consequently modify the physical, mechanical, conductive and chemical properties of the bulk soil matrix. In recent years, the topic of bio‐mediated geotec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(11 citation statements)
references
References 212 publications
(262 reference statements)
0
9
1
1
Order By: Relevance
“…Urea hydrolysis, which is triggered by aerobic ureolytic bacteria (e.g., Sporosarcina pasteurii, Lysinibacillus sphaericus, and Bacillus sphaericus) (Sigurdarson et al, 2018;Jiang et al, 2021), drives the transformation of urea to NH 4 + in soil (Vlek et al, 1980;Svane et al, 2020). Neem leaf extract used in the current study proved to be a stimulator of urea hydrolysis, in contrast to other studies whose findings indicated inhibitory effects (Sahrawat, 1980;Prasad and Power, 1995;Varel, 1997).…”
Section: Urea Hydrolysiscontrasting
confidence: 72%
“…Urea hydrolysis, which is triggered by aerobic ureolytic bacteria (e.g., Sporosarcina pasteurii, Lysinibacillus sphaericus, and Bacillus sphaericus) (Sigurdarson et al, 2018;Jiang et al, 2021), drives the transformation of urea to NH 4 + in soil (Vlek et al, 1980;Svane et al, 2020). Neem leaf extract used in the current study proved to be a stimulator of urea hydrolysis, in contrast to other studies whose findings indicated inhibitory effects (Sahrawat, 1980;Prasad and Power, 1995;Varel, 1997).…”
Section: Urea Hydrolysiscontrasting
confidence: 72%
“…Heavy metal contamination not only raises sustainable concerns but also causes threats to human health and plants (Kumari et al, 2016;Jiang et al, 2019;Rahman et al, 2020;Chen et al, 2021a;Tan et al, 2022). In the past few decades, remediation methods including replacement, soil flushing, electrokinetic remediation, chemical precipitation, ion exchange, and phytoremediation were developed (Mena et al, 2016;Kumari et al, 2017;Kumari et al, 2018;Chen and Achal, 2019;Duarte-Nass et al, 2020;Ahenkorah et al, 2021;Hu L. et al, 2021;Jiang et al, 2021). However, they are usually time-consuming and may cause secondary pollution (Achal et al, 2012;Nancharaiah et al, 2016;Kappaun et al, 2018;Xue et al, 2022;Yan et al, 2021;Duan et al, 2021a;Cheng et al, 2021;Duan et al, 2021b).…”
Section: Introductionmentioning
confidence: 99%
“…Such heavy metal contamination remediation by the traditional soil flushing measure is deemed time-consuming and costly since heavy metal ions are easily adsorbed by soil particles, and intensive industrial activities further aggravate heavy metal contamination ( Yang et al, 2014 ; An et al, 2019 ; Kumar and Dwivedi, 2019 ; Bai et al, 2021 ; Cheng et al, 2021 ; Duan et al, 2021 ; Wei et al, 2021 ; Yuan et al, 2021 ; Chen et al, 2022b ). In the past few years, various remediation measures, including but not limited to physical, chemical, and biological measures, have been proposed to deal with heavy-metal contamination ( Dhami et al, 2013 ; Shashank et al, 2016 ; Qian et al, 2017 ; Rahman et al, 2020 ; Ahenkorah et al, 2021a ; Hu et al, 2021 ; Jiang et al, 2021 ; and Xue et al, 2022 ). Amongst the heavy metal contamination remediation measures, enzyme-induced carbonate precipitation (EICP) is an environmentally friendly, efficient, and sustainable measure.…”
Section: Introductionmentioning
confidence: 99%